Understanding Water-Stress Responses in Soybean Using Hydroponics System—A Systems Biology Perspective - Tripathi, Prateek; Rabara, Roel C.; Shulaev, Vladimir; Shen, Qingxi J.; Rushton, Paul J. (Frontiers in Plant Science, 2015)
The deleterious changes in environmental conditions such as water stress bring physiological and biochemical changes in plants, which results in crop loss. Thus, combating water stress is important for crop improvement to manage the needs of growing population. Utilization of hydroponics system in growing plants is questionable to some researchers, as it does not represent an actual field condition. However, trying to address a complex problem like water stress we have to utilize a simpler growing condition like the hydroponics system wherein every input given to the plants can be controlled. With the advent of high-throughput technologies, it is still challenging to address all levels of the genetic machinery whether a gene, protein, metabolite, and promoter. Thus, using a system of reduced complexity like hydroponics can certainly direct us towards the right candidates, if not completely help us to resolve the issue.